Market entry as a marketplace owner: when and why should you sell on your marketplace? - Jürgen Rösch (Journal of Business Economics, 2023)
The new Digital Market Act (DMA) of the European Union imposes stricter rules on gatekeeper platforms. While this affects only a few very large platforms, the discussion surrounding the implementation of the DMA offers valuable insights into the strategic behaviors of those gatekeeper platforms. A gatekeeper platform, for example, may enter its platform as a supplier, which may hurt existing third-party suppliers and restrict fair competition on the platform. This paper flips the academic discussion on whether marketplace owners should be allowed to sell on their marketplaces. It illustrates why this behavior is profitable for gatekeepers and how marketplace owners can apply this knowledge to improve their business models. The paper identifies five situations in which becoming a supplier in one's marketplace can be profitable, but it also proposes alternative solutions to entering the market.
Keywords: M21; M30; M13; L26; L15; 650; Digital platforms; Digital Market Act; Self-preferencing; Market-entry; Marketplaces